Coinage metal aluminyl complexes: probing regiochemistry and mechanism in the insertion and reduction of carbon dioxide. Issue 40 (23rd September 2021) - McManus, Caitilín; Hicks, Jamie; Cui, Xianlu; Zhao, Lili; Frenking, Gernot; Goicoechea, Jose M.; Aldridge, Simon
Abstract : The differential reactivity of copper, silver and gold aluminyl compounds towards CO2 and other heteroallenes are probed by experimental and quantum chemical methods. Abstract : The synthesis of coinage metal aluminyl complexes, featuring M–Al covalent bonds, is reported via a salt metathesis approach employing an anionic Al(i ) ('aluminyl') nucleophile and group 11 electrophiles. This approach allows access to both bimetallic (1 : 1) systems of the type ( t Bu3 P)MAl(NON) (M = Cu, Ag, Au; NON = 4, 5-bis(2, 6-diisopropylanilido)-2, 7-di- tert -butyl-9, 9-dimethylxanthene) and a 2 : 1 di(aluminyl)cuprate system, K[Cu{Al(NON)}2 ]. The bimetallic complexes readily insert heteroallenes (CO2, carbodiimides) into the unsupported M–Al bonds to give systems containing a M(CE2 )Al bridging unit (E = O, NR), with the μ-κ 1 (C):κ 2 (E, E′) mode of heteroallene binding being demonstrated crystallographically for carbodiimide insertion in the cases of all three metals, Cu, Ag and Au. The regiochemistry of these processes, leading to the formation of M–C bonds, is rationalized computationally, and is consistent with addition of CO2 across the M–Al covalent bond with the group 11 metal acting as the nucleophilic partner and Al as the electrophile. While the products of carbodiimide insertion are stable to further reaction, their CO2 analogues have the potential to react further, depending on the identity of the group 11 metal. ( t Bu3 P)Au(CO)2 Al(NON) is inert to further reaction, but its silver counterpart reacts slowly with CO2 to give the corresponding carbonate complex (and CO), and the copper system proceeds rapidly to the carbonate even at low temperatures. Experimental and quantum chemical investigations of the mechanism of the CO2 to CO/carbonate transformation are consistent with rate-determining extrusion of CO from the initially-formed M(CO)2 Al fragment to give a bimetallic oxide that rapidly assimilates a second molecule of CO2 . The calculated energetic barriers for the most feasible CO extrusion step (Δ G ‡ = 26.6, 33.1, 44.5 kcal mol −1 for M = Cu, Ag and Au, respectively) are consistent not only with the observed experimental labilities of the respective M(CO)2 Al motifs, but also with the opposing trends in M–C (increasing) and M–O bond strengths (decreasing) on transitioning from Cu to Au.